Pengaruh Literasi Keuangan dan Inklusi Keuangan terhadap Keputusan Investasi Mahasiswa Universitas Muhammadiyah Palopo - Hildawati Nurdin; Asriany; Jumawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze the impact of financial literacy and financial inclusion on investment behavior. The study uses a quantitative method approach, with a population of 160 and a sample of 62 respondents taken from the Slovin formula. Data was collected through questionnaires and analysis using validity tests, reliability tests, multiple linear regression analysis results, T tests, F tests, R2 tests. Shows that investment, but financial inclusion has a significant influence on investment decisions, and financial education and financial inclusion simultaneously have a significant influence on investment decisions.